Bildung - Medien - Mensch. Mündigkeit im Digitalen - Missomelius, Petra (2021)
The book outlines education under the auspices of digitization. Transformation processes are highlighted which, triggered by binary technologies, reach deep into everyday cultures and worldviews in our societies. These challenge the basis for knowledge and education.